Effects of a Scaffolding Problem-Solving Model on Students’ Problem-Solving Abilities in Work and Energy - Rosa Filiyani; Rifa'atul Maulidah; Ernita Susanti (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
A preliminary study's findings, which showed that pupils at SMA Negeri 7 Tasikmalaya had poor problem-solving abilities with an average score of only 32% in the low category, served as the impetus for this investigation. Determining the impact of using scaffolding problem-solving model on the material of effort and energy in class X at SMA Negeri 7 Tasikmalaya during the 2024/2025 academic year was the aim of this study. The methodology used was a quasi-experiment with a matching only posttest only control group design. 433 students made up the study population, and two classes X-7 and X-8 were purposefully chosen as a sample. Measurement of problem-solving ability was carried out through a descriptive test. At a 0.05 threshold of significance, the hypothesis findings test using the t-test revealed that the tcount (5.341) was greater than the ttable (1.669), so Ha was accepted. The scaffolding problem solving model has been shown to provide gradual assistance, encourage activeness, systematic thinking, and evaluation of student solutions. Thus, it can be concluded that this model is influential in addressing problem-solving abilities in work and energy materials.